Promoción y turismo cultural en el cantón Guano, provincia de Chimborazo - Balladares Balladares, Jesus Alexander (2025)
The purpose of this research was to analyze the impact of promotion strategies on cultural tourism in the Guano canton, highlighting how brand image, advertising, and marketing management contribute to attracting visitors. To achieve this, a quantitative approach was adopted, with a descriptive and correlational design. Data was collected through surveys administered to tourists and officials of the Guano tourism department, evaluating key aspects such as the perception of the brand image and the effectiveness of advertising. The results showed that, although Guano has high tourism potential, current promotion is insufficient, and many respondents are unaware of the existence of a consolidated tourism brand for the canton. In addition, it was observed that both advertising and an appropriate marketing strategy are essential factors to attract visitors and promote recognition of the destination. Correlation tests confirmed that there is a positive relationship between effective marketing management and increased visits. In conclusion, it is recommended to strengthen Guano's brand image and use digital promotion strategies, taking advantage of online platforms to attract a broader audience interested in cultural experiences. Thus, the canton will be able to position itself as an attractive and competitive cultural destination, promoting tourism development and the preservation of its cultural heritage.